Engineering, biochemical, and cooking characteristics of seven eminent cultivars of brown rice: Implication on development of food processing equipment. (1st May 2022) - Bhati, Dolly; Singh, Baljit; Singh, Arashdeep; Sharma, Savita; Pandiselvam, Ravi
Abstract: The objective of the present investigation was to substantiate the versatility of brown rice obtained from distinguished Indian varieties with a viable hyphenation with the cultivar influences. Brown rice from seven eminent cultivars, that is, PR‐114, PR‐121, PR‐122, PR‐123, PR‐124, PR‐126, and PR‐127, was in depth characterized by a broad spectrum of properties. Primarily, to comprehend the suggestive milling behavior of paddy and brown rice, their dimensional and physical properties were compared. Secondly, to validate the physicofunctional and cooking prominence of the grain, properties such as amylose and amylopectin content, alkali spreading value (ASV), temperature, and behavior of gelatinization were scrutinized. The assessment of specific nutritional components viz., mineral, vitamins, and fatty acid composition together with textural profile analysis of the cooked grain further validated the primacy of the Indian cultivars. The result presented that the physical and dimensional characteristics of paddy and brown rice varied significantly. In terms of physicochemical and cooking properties, the cultivars PR‐122 and PR‐124 demonstrated considerable pre‐eminence. Furthermore, the ASV, temperature, and gelatinization behavior were principally associated with the starch constituents, that is, amylose and amylopectin. With reference to the mineral, vitamins, and fatty acid composition of the cultivars, PR‐122, PR‐122, and PR‐124 were nutritionally and functionally viable and diverse. Practical applications: Brown rice is a nutritionally and biofunctionally eminent cereal grain. A viable hyphenation between the anticipated properties demonstrated by these improved and high‐yielding brown rice varieties grown in India would further endorse the cultivation of these cultivars at a larger scale as well as invigorated the farmers to fast‐track their cultivation estate. The physical, physicochemical, gelatinization, cooking, and textural properties of the Indian brown rice cultivars could play a vital role in deciphering and substantiating its processing, nutritional and bio‐viable eminences, which would further confirm their superior demands in the context of regional and national food markets along with food processing industries operating at variable scales.